Professional cloud architect : Google cloud certification guide : a handy guide to designing, developing, and managing enterprise-grade GCP cloud solutions /: Google cloud certification guide : a handy guide to designing, developing, and managing enterprise-grade GCP cloud solutions. (2019) - Clapa, Konrad; Gerrard, Brian
No abstract available